2017
DOI: 10.1128/mbio.00373-17
|View full text |Cite
|
Sign up to set email alerts
|

Further Evidence for Bats as the Evolutionary Source of Middle East Respiratory Syndrome Coronavirus

Abstract: The evolutionary origins of Middle East respiratory syndrome (MERS) coronavirus (MERS-CoV) are unknown. Current evidence suggests that insectivorous bats are likely to be the original source, as several 2c CoVs have been described from various species in the family Vespertilionidae. Here, we describe a MERS-like CoV identified from a Pipistrellus cf. hesperidus bat sampled in Uganda (strain PREDICT/PDF-2180), further supporting the hypothesis that bats are the evolutionary source of MERS-CoV. Phylogenetic anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
322
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 293 publications
(338 citation statements)
references
References 64 publications
15
322
0
1
Order By: Relevance
“…Bats are reservoirs of several emerging RNA viruses, such as filoviruses (ebolavirus and Marburg virus), paramyxoviruses (Nipah and Hendra viruses), and coronaviruses (severe acute respiratory syndrome [SARS] and Middle East respiratory syndrome [MERS] coronaviruses [CoVs]) that cause serious and often fatal disease in humans and agricultural animals (Anthony et al, 2017;Forbes et al, 2019;Ge et al, 2013;Swanepoel et al, 2007;Yang et al, 2019). More recently, SARS-CoV-2, which is causing the ongoing COVID-19 outbreak, was determined to be 96% similar at the genomic level to a bat CoV (Bat_CoV_RaTG13) that was detected in Rhinolophus affinis (Zhou et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Bats are reservoirs of several emerging RNA viruses, such as filoviruses (ebolavirus and Marburg virus), paramyxoviruses (Nipah and Hendra viruses), and coronaviruses (severe acute respiratory syndrome [SARS] and Middle East respiratory syndrome [MERS] coronaviruses [CoVs]) that cause serious and often fatal disease in humans and agricultural animals (Anthony et al, 2017;Forbes et al, 2019;Ge et al, 2013;Swanepoel et al, 2007;Yang et al, 2019). More recently, SARS-CoV-2, which is causing the ongoing COVID-19 outbreak, was determined to be 96% similar at the genomic level to a bat CoV (Bat_CoV_RaTG13) that was detected in Rhinolophus affinis (Zhou et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The highly pathogenic human coronaviruses SARS-CoV and MERS-CoV originated in bat zoonotic reservoirs and then passed through different intermediate hosts prior to infecting humans. Bat coronavirus strains that share varying homology to MERS-and SARS-CoV are still circulating and represent the pre-epidemic strains most likely to make the jump into humans (Anthony et al, 2017;Becker et al, 2008;Menachery et al, 2015Menachery et al, , 2016Sheahan et al, 2008aSheahan et al, , 2008b. As many novel bat coronavirus strains were identified solely as genomic sequence isolated from bat guano, characterization of these strains beyond sequence analysis was not initially possible.…”
Section: Hot Topics and Late-breakersmentioning
confidence: 99%
“…Bats are considered natural reservoirs for several zoonotic viruses including lyssaviruses (Davis et al, 2013a, b;Albas et al, 2011;Almeida et al, 2011Almeida et al, , 2005, henipaviruses (Roche et al, 2015;Breed et al, 2011;Rahman et al, 2010), coronaviruses (Anthony et al, 2017; T coronavirus (MERS-CoV) that was first reported in Saudi Arabia , and severe acute respiratory syndrome coronavirus (SARS-CoV) that caused outbreaks in China in 2003 (Ge et al, 2016(Ge et al, , 2013Balboni et al, 2012;Wang et al, 2006). A novel coronavirus, which is closely related to SARS-CoV and uses Angiotensin Converting Enzyme 2 (ACE-2) receptor from humans, civets, and Chinese horseshoe bats for cell entry, was isolated from Chinese horseshoe bats suggesting these bats might be natural reservoirs of SARS-CoV (Ge et al, 2013).…”
Section: Introductionmentioning
confidence: 99%